Methodology for the Construction of a Disease Nomenclature and Classification System for Clinical Use - Kiuchil, T.; Ohashi, Y.; Sato, H.; Kaihara, S. (Methods of Information in Medicine, 1995)
The nature and problems of the linguistic representation of clinical data are discussed, using the linguistic theory of Ferdinand de Saussure. Based on the conclusions, a methodology for the construction of a disease nomenclature and a classification system, suitable for use in clinical information systems, is developed using set theory.
Keywords: Linguistics; Nomenclature; Clinical information system; Set theory